Application of Mesenchymal Stem Cell Intended to Investigate the Reward Response of Nucleus Accumbens in a Local Demyelination Model of Rat - M. Goodarzvand; K. Rahampour; P. Azizi; M.A. Sherafat; A. Nazari-Boroon; A. Haghparast; S. Taheri (Bihdād, 2014)
Introduction: Demyelination is the most common complication of multiple sclerosis in that the myelin sheaths around the axons and cerebral nucleus are damaged. The accumbens nucleus is a part of the striatum of the CNS that has role in reward response. Recently, stem cell therapy has been considered by many researchers. Therefore, the aim of this study was application of mesenchymal stem cells to assess demyelination (apoptosis), remyelination (neuronal differentiation) and reward response of accumbens nucleus in a local demyelination model. Method and Materials: Male Wistar rats weighting 250-300 gr were anesthetized with chloral hydrate. Ethidium bromide was directly injected into the nucleus accumbens. A thin canola was mounted into the ventricle coordination, simultaneously. Animals were divided into 4 groups: Control (received saline as solvent of EB), sham, PBS 14 and 28 (received PBS as vehicle of stem cell) and experiments 14 and 28 (received mesenchymal 5* 100000 of stem cells). Conditioned Place Preference (CPP) was done in days zero, 14 and 28 post surgery and morphine was subcutaneously injected to assess reward response. Results: This study showed CCP increment in experiment groups compared to PBS ones, significantly. Discussion: The results of the present study suggesting stem cell therapy as an effective factor to swift the healing processes of the CNS and to improve reward response should be considered.